Nested matched case control study for the Japan Fukushima Health Management Survey's first full-scale (second-round) thyroid examination. Issue 27 (2nd July 2020) - Takahashi, Hideto; Yasumura, Seiji; Takahashi, Kunihiko; Ohira, Tetsuya; Ohtsuru, Akira; Midorikawa, Sanae; Suzuki, Satoru; Shimura, Hiroki; Ishikawa, Tetsuo; Sakai, Akira; Suzuki, Shinichi; Yokoya, Susumu; et al.
Abstract : Abstract: Since Fukushima nuclear accident in 2011, thyroid ultrasound examinations have been conducted. The first full-scale examination detected 71 thyroid-cancer cases. This study examined whether radiation exposure was associated with thyroid-cancer incidence. Subjects were participants in the baseline screening and newborns during the 2011 fiscal year. Under nested matched case-control study design, 10 controls per each case were selected by matching the age, sex, baseline screening results, and interval between examinations. With 3 dose levels of external radiation: 1.3 + mSv (upper), 0.8 to 1.3 (middle), and 0.0 to 0.8 (reference), we applied 2 logistic models adjusting for 3 participation-proportions (primary, secondary, and fine-needle aspiratory cytology), overweight, and the B-result of baseline screening (Model 1), and past medical history, family history of thyroid cancer, and frequencies of eating seafood and seaweed in addition to the parameters in Model 1 (Model 2). We examined each model in 3 ways: (a) excluding subjects with a missing radiation exposure dose; and substituting (b1) median or (b2) mean dose of the municipality with missing dose. Odds ratios (ORs) of middle-dose exposure were (a) 1.35 (0.46–3.94), (b1) 1.55 (0.61–3.96), and (b2) 1.23 (0.50–3.03) for Model 1, and (a) 1.18 (0.39–3.57), (b1) 1.31 (0.49–3.49), and (b2) 1.02 (0.40–2.59) for Model 2. For upper-dose exposure, similar results were obtained. Past medical history was significantly associated (odds ratio  = 2.04–2.08) with both (b1) and (b2) in Model 2. No significant associations were obtained between the external radiation exposure and thyroid-cancer incidence. Abstract : Supplemental Digital Content is available in the text